Gas Barrier Coating Film
A polyvinyl alcohol and polyacrylic acid-based coating with carbodiimide addresses the high oxygen transmission and mechanical issues of PVOH coatings, providing efficient and recyclable gas barrier performance at low temperatures.
Patent Information
- Application Number
- JP2024531500
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-07
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-19
AI Technical Summary
Current gas barrier coatings for food packaging, such as those using PVOH, face issues with high oxygen transmission rates at high humidity, require energy-intensive metallization processes, compromise mechanical properties, and are not recyclable, with fillers leading to poor dispersion and flexibility problems.
A barrier coating comprising polyvinyl alcohol, polyacrylic acid, and carbodiimide is formed at low temperatures, maintaining mechanical properties and recyclability without the need for high curing temperatures or additional coatings.
The coating achieves low oxygen transmission rates at high humidity, is energy-efficient, and maintains mechanical integrity while being recyclable, addressing the limitations of existing PVOH-based coatings.
Smart Images

Figure 2024546236000001 
Figure 2024546236000002 
Figure 2024546236000003
Abstract
Description
[Technical field]
[0001] Priority This application claims the benefit of International Application No. PCT / CN2021 / 136058, filed December 7, 2021.
[0002] The present disclosure relates to gas barrier coatings used in food production and storage. More specifically, the present disclosure relates to PVOH-containing gas barrier coatings used in food production and storage.
[0003] Introduction The freshness and quality of packaged foods are maintained by limiting oxygen and moisture permeability. Currently, plastic packaging is metallized or coated with thick gas barrier polymers such as PVOH, EVOH, or nylon. Metallization is an energy intensive process. When metallization is used, an additional processing step is added, requiring the application of a primer coating. The amount of these added materials also negatively impacts recyclability. In addition, when PVOH is used, the oxygen transmission rate (OTR) increases at high humidity. Fillers can increase the tortuosity of the path taken by the gas diffusing molecules, but can also lead to poor dispersion within the polymer matrix and poor mechanical properties such as flexibility of the final packaging film. Attempts have also been made to crosslink PVOH, but this can result in high cure temperatures that can damage the underlying plastic film or commercially unviable cure times.
[0004] Therefore, there is a need for gas barrier coatings that are low energy intensive, are recyclable, have good OTR at high humidity, do not compromise the mechanical properties of the final film, and do not require high cure temperatures or commercially unviable cure times. Summary of the Invention
[0005] A barrier coating is disclosed that includes polyvinyl alcohol, polyacrylic acid, and a carbodiimide, where the barrier film is formed at less than 120° C. Also disclosed is a laminate that includes the barrier coating that includes polyvinyl alcohol, polyacrylic acid, and a carbodiimide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed.
[0007] Numerical ranges disclosed herein include all values between the lower limit and the upper limit (inclusive). In the case of ranges containing explicit values (e.g., ranges 1, or 2, or 3-5, or 6, or 7), any subranges between any two explicit values are included (e.g., the range 1-7 above includes the subranges 1-2, 2-6, 5-7, 3-7, 5-6, etc.).
[0008] The term "composition" refers to a mixture of materials that make up the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0009] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term polymer encompasses the term homopolymer (used to refer to a polymer prepared from only one type of monomer), and the terms copolymer or interpolymer. Trace amounts of impurities (e.g., catalyst residues) may be incorporated in and / or within the polymer. The polymer may be a single polymer, a polymer blend, or a polymer mixture, including a mixture of polymers formed in situ during polymerization.
[0010] As used herein, the term "polyolefin" means a polymer that contains, in polymerized form, a majority of olefin monomers, such as ethylene or propylene (based on the weight of the polymer), and may optionally contain one or more comonomers.
[0011] "Polyethylene polymer", "polyethylene-based polymer", "PE-based polymer", "polyethylene", or "ethylene-based polymer" is intended to mean a polymer that contains a majority of units derived from ethylene monomer (>50 mol%, or >60 mol%, or >70 mol%, or >80 mol%, or >90 mol%, or >95 mol%, or >97 mol%). This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), very low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), which includes both linear and substantially linear low density resins, medium density polyethylene (MDPE), and high density polyethylene (HDPE). These polyethylene materials are generally well known in the art. However, the following description may be helpful in understanding the differences between some of these different polyethylene resins.
[0012] The term "LDPE", which may also be referred to as "high pressure ethylene polymer", or "highly branched polyethylene", is defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator, such as a peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated herein by reference). LDPE resins typically have a density in the range of 0.916 to 0.935 g / cm3.
[0013] The term "LLDPE" includes both resins made using traditional Ziegler-Natta and chromium-based catalyst systems, as well as single-site catalysts, including, but not limited to, bis-metallocene catalysts (sometimes referred to as "m-LLDPE") and constrained geometry catalysts, and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers, as further defined in U.S. Patents 5,272,236, 5,278,272, 5,582,923, and 5,733,155; homogeneously branched linear ethylene polymer compositions, such as those in U.S. Patent 3,645,992, heterogeneously branched ethylene polymers, such as those prepared according to the process disclosed in U.S. Patent 4,076,698, and / or blends thereof, such as those disclosed in U.S. Patents 3,914,342 or 5,854,045. LLDPE can be made via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0014] The term "MDPE" refers to polyethylene having a density of 0.926 to 0.935 g / cm3. "MDPE" is typically made using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including but not limited to bis-metallocene catalysts and constrained geometry catalysts, and typically has a molecular weight distribution (MWD) greater than 2.5.
[0015] The term "HDPE" refers to polyethylene having a density greater than about 0.935 g / cm3 to about 0.970 g / cm3 that is generally prepared using a single-site catalyst, including, but not limited to, Ziegler-Natta, chromium, or bis-metallocene and constrained geometry catalysts.
[0016] The term "ULDPE" generally refers to polyethylene having a density between 0.880 and 0.912 g / cm3 that is prepared with a single-site catalyst, including but not limited to Ziegler-Natta, chromium, or bis-metallocene and constrained geometry catalysts.
[0017] "Polypropylene-based polymer", "PP-based polymer", or "polypyrene-based polymer" is intended to mean a polymer that contains a majority (>50 mol%, or >60 mol%, or >70 mol%, or >80 mol%, or >90 mol%, or >95 mol%) of units derived from polypyrene monomers.
[0018] "Polyethylene terephthalate-based polymer" or "PET-based polymer" shall mean a polymer that contains a majority amount (>50% by weight, or >60% by weight, or >70% by weight, or >80% by weight, or >90% by weight, or >95% by weight) of ethylene terephthalate.
[0019] A "polyolefin plastomer" can be a polyethylene plastomer or a polypropylene plastomer. Polyolefin plastomers include, for example, polymers made using single-site catalysts, such as metallocene and constrained geometry catalysts. Polyolefin plastomers have a viscosity of 0.885 to 0.915 g / cm 3 It has a density of 0.885g / cm 3 ~0.915g / cm 3 All individual values and subranges are included herein and disclosed herein. For example, the density of a polyolefin plastomer may be 0.895, 0.900, or 0.905 g / cm 3 from the lower limit of 0.905, 0.910, or 0.915 g / cm 3 In some embodiments, the polyolefin elastomer has a viscosity of 0.890 to 0.910 g / cm 3 has a density of
[0020] The "polyolefin elastomer" may be a polyethylene elastomer or a polypropylene elastomer. The polyolefin elastomer has a modulus of 0.857 to 0.885 g / cm 3 It has a density of 0.857g / cm 3 ~0.885g / cm 3 All individual values and subranges are included herein and disclosed herein. For example, the density of the polyolefin elastomer may be 0.857, 0.860, 0.865, 0.870, or 0.875 g / cm. 3 From the lower limit of 0.870, 0.875, 0.880, or 0.885 g / cm 3 In some embodiments, the polyolefin elastomer has a viscosity of 0.860 to 0.880 g / cm 3 has a density of
[0021] "Polyethylene-based film" or "PE-based film" refers to a film that contains at least 90 weight percent polyethylene, at least 95 weight percent polyethylene, or at least 97 weight percent polyethylene, based on the total weight of the film.
[0022] "Polypropylene-based film" or "PP-based film" refers to a film that contains at least 90 weight percent polypropylene, at least 95 weight percent polypropylene, or at least 97 weight percent polypropylene, based on the total weight of the film.
[0023] "Polyethylene terephthalate-based film" or "PET-based film" refers to a film that contains at least 90 weight percent polyethylene terephthalate, at least 95 weight percent polyethylene terephthalate, or at least 97 weight percent polyethylene terephthalate, based on the total weight of the film.
[0024] As used herein, an antioxidant is a compound that is included in a polymer film to stabilize the polymer(s) or prevent oxidative degradation of the polymer(s). Antioxidants are well known to those skilled in the art.
[0025] As used herein, an anti-blocking agent is a compound that minimizes or prevents sticking (i.e., adhesion) between two adjacent layers of a film. Sticking can cause problems, for example, during unwinding of a film roll. The use of anti-blocking agents is well known to those skilled in the art. Examples of common anti-blocking agents include, but are not limited to, silica, talc, calcium carbonate, and combinations thereof.
[0026] As used herein, a slip agent is a compound added to a film to reduce friction between the film and / or between the film and the equipment. Typical slip agents include migratory and non-migratory slip agents and are well known to those skilled in the art.
[0027] As used herein, the term "copolymer" means any polymer having two or more monomers.
[0028] As used herein, the term "polyvinyl alcohol" means a polymer of vinyl alcohol.
[0029] Barrier Coating Disclosed herein are barrier coatings in which the barrier film is formed at or below 120°C. The barrier coatings may include polyvinyl alcohol, polyacrylic acid, and a carbodiimide. The barrier coatings may have a polyvinyl alcohol to polyacrylic acid ratio of 95:5 to 5:95. All internal subranges and values are disclosed. For example, the barrier coatings may have a polyvinyl alcohol to polyacrylic acid ratio of 15:85 to 85:15, 30:70 to 70:30, or 50:50. The barrier coatings may include 5% by weight carbodiimide. The barrier coatings may include 0.5 to 10% carbodiimide. The barrier coatings may include aqueous coating additives such as, but not limited to, antiblocking agents, defoamers, thickeners, and wetting agents.
[0030] Substrates coated with a barrier coating have a humidity level of 0.60 cc / m at 50% or greater relative humidity. 2 Substrates coated with a barrier coating can have an OTR of 0.60 to 0.04 cc / m at 50% or greater relative humidity. 2 All internal values and subranges are disclosed. For example, a substrate coated with a barrier coating may have an OTR of 0.04 to 0.1 cc / m 2 The barrier coating may have an OTR of 10,000 MPa (15,000 psi).
[0031] The barrier coating may be formed at a temperature less than 120° C. The barrier coating may be formed at a temperature from 50 to 119.9° C. All internal values and subranges are disclosed. For example, the barrier coating may be formed at a temperature from 80 to 119.9° C.
[0032] Polyacrylic acid The polyacrylic acid may comprise at least one poly(meth)acrylic acid. The polyacrylic acid may comprise a copolymer of at least two polymers. The polyacrylic acid may comprise a copolymer of at least two monomers. The polyacrylic acid may comprise a mixture of at least two polymers.
[0033] Polyacrylic acid has a number average (M n ) molecular weight. All internal values and subranges are included. For example, polyacrylic acid may have a number average molecular weight (M) of 20,000 to 300,000 or 40,000 to 200,000 g / mol. n ).
[0034] The polyacrylic acid may be partially neutralized. The polyacrylic acid may have a degree of neutralization of 2-50%. All internal values and subranges are included. For example, the polyacrylic acid may have a degree of neutralization of 5-20%. The polyacrylic acid may be neutralized with NaOH, KOH, NH 3 H 2 It can be partially neutralized using bases including, but not limited to, O, ZnO, and CaO.
[0035] Polyvinyl alcohol The polyvinyl alcohol may have a degree of saponification of at least 80%. The polyvinyl alcohol may have a degree of saponification of at least 95%. The polyvinyl alcohol may have a degree of saponification of 80-100%. All internal values and subranges are included. For example, the polyvinyl alcohol may have a degree of saponification of 95-100%.
[0036] The polyvinyl alcohol can have a molecular weight of 10,000 to 300,000 g / mol. All internal values and subranges are disclosed. For example, the polyvinyl alcohol can have a molecular weight of 50,000 to 200,000 g / mol.
[0037] The polyvinyl alcohol resin has a degree of saponification of at least 80% and a molecular weight (M) of 10,000 to 300,000 g / mol. wThe polyvinyl alcohol may have a degree of saponification of at least 95% and a molecular weight (M) of 50,000 to 200,000 g / mol. w ).
[0038] Base material The substrate may include a film. The film may have at least one layer that includes polyethylene. The other layer may be PP, nylon, or other plastics known to those skilled in the art. There may be one layer. Alternatively, there may be two or more layers. These two or more layers may be extruded together to form a film. There may be three (or more) layers. When there are three (or more) layers, the outer layer is called the sealant layer, the layer opposite the sealant layer is called the skin layer, and the layer or layers between the skin layer and the sealant layer are the core layer or layers. When there is only one layer that includes, any of the compositions discussed herein as skin layer, core layer, or sealant layer may be used. When there are only two layers, any combination of skin layer and core layer, skin layer and sealant layer, or core layer and sealant layer may be used. When there are two or more layers, each layer may be directly adjacent to at least one other layer or adhesive layer. The film may include a sealant layer. The film may include a skin layer, a core layer, and a sealant layer.
[0039] The film may comprise linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), as well as combinations of two or more of the foregoing.The film may comprise Ziegler-Natta catalyzed, single-site catalyzed (including but not limited to metallocene), or chromium catalyzed linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), autoclave-produced or tubular-produced low density polyethylene (LDPE), as well as combinations of two or more of the foregoing.
[0040] The film may further comprise at least one of very low density polyethylene, polyolefin plastomer, polyolefin elastomer, ethylene vinyl acetate copolymer, ethylene ethyl acrylate copolymer, ethylene vinyl alcohol, and any polymer comprising at least 50% ethylene monomer, and combinations thereof.
[0041] The skin layer may include polypropylene, nylon, linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), and combinations of two or more of the foregoing. The LLDPE may be single-site catalyzed polyethylene (such as, but not limited to, m-LLDPE). The skin layer may further include additives such as, for example, antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblocking agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and blowing agents.
[0042] The core layer can include linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), as well as combinations of two or more of the foregoing.
[0043] The sealant layer may comprise linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), polyolefin elastomers or plastomers, as well as combinations of two or more of the foregoing. The sealant layer may comprise Ziegler-Natta, single-site (including metallocene), or chromium catalyzed linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), autoclave-produced or tubular-produced low density polyethylene (LDPE), as well as combinations of two or more of the foregoing. The LLDPE may be a single-site catalyzed polyethylene (e.g., mLLDPE). This may be an outer layer of the film. The sealant layer may advantageously comprise an antiblocking agent. For example, the antiblocking agent may be present in the sealant layer in an amount of at least about 200 ppm, at least about 1000 ppm, or at least about 1500 ppm. Additionally, slip agents (e.g., erucamide) may be useful. For example, the slip agent may be present in the sealant layer in an amount less than 500 ppm, or less than 300 ppm, or less than 200 ppm, less than 100 ppm, or equal to 0 ppm, based on the total weight of the sealant layer.
[0044] The film may be a blown film, a cast film, a longitudinally stretched film, or a biaxially stretched film. The film may be produced by blown, cast, water-cooled, double bubble, or other techniques known to those skilled in the art, such as those described in Film Processing Advances, Toshitaka Kanai and Gregory A. Campbell (editors), Chapter 7 (Biaxial Oriented Film Technology), pp. 194-229. After production, the film may be subjected to a machine direction orientation (MDO) or biaxial stretching process to provide a longitudinally stretched film or a biaxially stretched film, respectively.
[0045] The total thickness of the film can be at least 10 micrometers, at least 20 micrometers, or at least 30 micrometers. The total thickness of the film can be no more than 200 micrometers, no more than 150 micrometers, no more than 120 micrometers, no more than 100 micrometers, no more than 80 micrometers, no more than 70 micrometers, or no more than 60 micrometers.
[0046] The concentration of the antioxidant in the film layer is less than 3000 ppm, or less than 2000 ppm, or less than 1500 ppm, or less than 1300 ppm, based on the total weight of the film.
[0047] Production and Use Solutions of PVOH and various bases can be obtained as understood in the art. Partially neutralized PAA can be prepared by adding a calculated amount of base solution to the PAA solution. The amount of base added depends on the desired degree of neutralization and the moles of PAA carboxyl groups present in the sample to be neutralized. The partially neutralized PAANa and PVOH can then be mixed by various methods understood in the art to obtain a barrier coating.
[0048] The solutions thus produced can be coated onto a variety of substrates, such as polyethylene, polypropylene, or polyethylene terephthalate, using a variety of means known in the art, such as bar coating, at various film thicknesses depending on the application. The resulting coated substrates are useful in food packaging as well as any other application where an oxygen impermeable barrier is required.
[0049] Test procedure Vapor sorption Vapor sorption is measured using a VTI-SA+ vapor sorption analyzer from TA Instruments. Thin film samples are peeled from the substrate and dried at 60°C for 24 hours. The equilibrium weight for each sample from 0% to 80% RH at 10% RH intervals is then measured at 25°C with an equilibration criterion of 0.0010 wt% within 5 minutes and a maximum equilibration time of 180 minutes at each condition. Vapor sorption is calculated from the difference between the equilibration weight at each condition and the dry weight of the film and is expressed as a percentage.
[0050] OTR measurement The oxygen transmission rate of the blend films was measured at 23° C. and 50% relative humidity according to ASTM D3985-05 using a MOCON Ox-Tran Model 2 / 21.
[0051] WVTR measurement WVTR measurements are performed on a Mocon Permatran-W™ Model 3 / 33 using the wet sponge method (100% RH) at 37°C. The test area is 50 cm 2 The test procedure was in accordance with ASTM F1249. EXAMPLES
[0052] Table 1 lists the materials used in the following examples. All DOW™ products are available from DOW™ chemical.
[0053] [Table 1]
[0054] Preparation of PVOH thin films Prepare a 12 wt% PVOH solution by dissolving 24 grams of PVOH powder in 176 grams of deionized water for 2 hours at 95° C. Mix the crosslinker and filler with the solution using a FlackTek Mixer at 2000 rpm for 2-5 minutes.
[0055] Coating Procedure The prepared formulation is dispensed onto a PE or PET substrate with a pipette and spread with a 3 mil BYK drawdown bar. The coated sample is then dried in an oven at 90°C for 1 hour to obtain a dry film of approximately 9 μm.
[0056] [Table 2]
Claims
1. 1. A barrier coating comprising polyvinyl alcohol, polyacrylic acid, and a carbodiimide, wherein the barrier film is formed at less than 120°C.
2. 10. The barrier coating of claim 1, wherein the polyacrylic acid comprises at least one poly(meth)acrylic acid.
3. 3. The barrier coating of claim 1 or 2, wherein the polyacrylic acid has a molecular weight of 2000 to 400,000 g / mol.
4. A barrier coating according to any of claims 1 to 3, wherein the polyacrylic acid has a molecular weight of 20,000 to 300,000 g / mol.
5. 5. The barrier coating of claim 1, wherein the polyacrylic acid has a molecular weight of 40,000 to 200,000.
6. 6. The barrier coating of claim 1, wherein the polyacrylic acid is partially neutralized.
7. 7. The barrier coating of claim 1, wherein the polyacrylic acid has a degree of neutralization of 2-50%.
8. A barrier coating according to any of claims 1 to 7, wherein the polyvinyl alcohol has a degree of saponification of at least 80%.
9. 9. A barrier coating according to any of claims 1 to 8, wherein the polyvinyl alcohol has a degree of saponification of at least 95%.
10. A barrier coating according to any of the preceding claims, wherein the polyvinyl alcohol has a molecular weight of 10,000 to 300,000 g / mol.
11. A barrier coating according to any of the preceding claims, wherein the polyvinyl alcohol has a molecular weight of 50,000 to 200,000 g / mol.
12. 12. A barrier coating according to any preceding claim having a polyvinyl alcohol to polyacrylic acid ratio of from 95:5 to 5:
95.
13. 13. A barrier coating according to any of the preceding claims having a polyvinyl alcohol to polyacrylic acid ratio of from 15:85 to 85:
15.
14. 13. A laminate comprising the barrier coating of claim 1.
Citation Information
Patent Citations
Carbodiimide crosslinking agent, its production and coating material
JP1998316930A
Gas-barrier coating agent and gas-barrier film
JP2001164174A
Gas barrier material excellent in resistance to retort- packing
JP2002302150A
Gas barrier composition, coating agent and film
JP2004018650A
Gas-barrier coating agent and gas barrier film using it
JP2005060621A
